Girls’ Emotional and Meaningful Attitude to Motherhood - Burmenskaya G.V. (Консультативная психология и психотерапия, 2018)
We carried out the conditions analysis of the development of emotional and meaningful attitude to motherhood among student-age girls in connection with low fertility and ambiguous attitude of young people to parenting — a pressing problem in present-day Russia. The presented results of the empirical study (N=230) identify five types of girls ‘ attitude to motherhood and show their relationship with the peculiarities of parent-child interaction in the parent family. The unfavorable tendency of negative and ambivalent attitude to motherhood was revealed in a significant part of the sample. The formation of positive emotional and meaningful attitudes towards the birth of children in girls is facilitated by parental acceptance, cooperation, closeness, consent, as well as the authority of parents and satisfaction with relations with them. Disharmonious child-parent relationships are more often found in girls that reject a mother’s role. The role of a sibling position is considered, as well as a factor of girls’ living together with parents or separately.